From Valletta to Faro: Archaeological Heritage and Communities - Poškienė, Justina (Archaeologia Lituana, 2025)
The article discusses the changing trends in archaeological heritage conservation – from expertise-based heritage protection to the ‘democratisation of heritage’. This process is well represented by the Amersfoort Agenda, adopted by The Europae Archaeologiae Consilium (EAC) in 2014, which seeks to integrate the principles of the Faro Convention into the practice of archaeological heritage protection developed by the Valletta Convention. More generalised heritage conservation processes and changes in public administration policies that promote participatory (interactive) governance also contribute to a stronger role for society in decision-making. It is in this aspect – the relationship between archaeology and society – that the paper presents the contemporary trends in archaeological heritage conservation, as well as insights into the local communities’ attitudes towards archaeological heritage in Lithuania.
Keywords: archaeological heritage; heritage communities; Faro Convention; Valletta Convention; Amersfoort Agenda